Efektivitas Penambahan Terapi Laser Intensitas Tinggi (High-Intensity Laser Therapy / HILT) terhadap Latihan Fisik dalam Mengurangi Nyeri, Meningkatkan Kekuatan Otot, dan Memperbaiki Kemampuan Fungsional pada Pasien dengan Osteoartritis Lutut: Suatu Uji A - Rizki, Laksmana; Z. Tamin, Tirza; Anestherita, Fitri; Handoko, Harrison (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2025)
Introduction: Osteoarthritis (OA) is a leading cause of disability worldwide, impacting patient’s daily functional abilities as well as quality of life due to chronic pain associated with joint damage. High-Intensity Laser Therapy (HILT) has been proven effective in reducing pain and improving function in patients with knee OA. Despite its recognition as a safe and effective modality, standardized protocols for its use in knee OA are lacking. This study aims to evaluate the effectiveness of incorporating HILT in addition to physical exercise programs for patients with knee OA.Methods: 30 patients with knee OA were randomized into 2 groups, HILT + physical exercise (intervention group), and physical exercise only (control group). Visual Analogue Scale (VAS), quadriceps and hamstring muscle strength using exercise testing, and functional ability using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaire were measured and compared.Result: Both groups displayed statistically significant improvement in pain, muscle strength, and functional ability by the end of the program (week 4) compared to the initial examination (p less than 0.05). When compared, there was a significant difference in pain reduction and functional ability in favor of the intervention group (p less than 0.05). However, there were no significant differences in quadriceps and hamstring muscle strength between the groups (p=0.148 and p=0.345, respectively).Conclusion: In this study, it was shown that the combination of HILT and physical exercise was more effective in alleviating pain and enhancing functional ability in patients with knee OA compared to physical exercise alone.